Perlindungan Hukum terhadap Pekerja Migran Indonesia Non-Prosedural Asal Kabupaten Indramayu dalam Perspektif Hak Asasi Manusia - Putri Desi Nurlaeli (Lembaga Teewan Journal Solutions, 2026)
The increasing number of non-procedural Indonesian Migrant Workers (PMI) reflects persistent legal protection challenges in Indonesia's migrant worker governance. This study analyzes the factors driving Indramayu workers to migrate non-procedurally to Malaysia and examines the state's legal protection policies from a human rights perspective. Using empirical legal methods with a socio-legal approach, primary data were collected through interviews with non-procedural migrant workers and stakeholders, while secondary data were obtained from literature and regulatory reviews. The findings reveal that economic pressure, limited employment, low legal awareness, and broker influence are the main push factors. Although Indonesia has established Law Number 18 of 2017 on Migrant Worker Protection, its implementation remains administrative and focuses on documented workers. Consequently, non-procedural workers have limited access to preventive legal protection and are typically assisted only after problems arise. From a human rights perspective, every migrant worker is entitled to state protection regardless of administrative status. Strengthening preventive protection mechanisms, improving legal awareness, enhancing institutional coordination, and developing inclusive protection policies are essential to fulfill migrant workers' fundamental rights.